Estimation of genetic and phenotypic trends for wool traits in Kashmir Merino sheep - HAMADANI, AMBREEN; GANAI, NAZIR A; RATHER, M A; RAJA, T A; SHABIR, N; AHMAD, TAVSIEF; SHANAZ, S; AALAM, S; SHABIR, M (The Indian Journal of Animal Sciences, 2020)
A study was planned to estimate genetic, heritability and phenotypic trends for Kashmir Merino sheep of J&K. The present study was carried out to study the genetic and phenotypic trends of various wool traits of this breed to understand its progress over the years. Phenotypic, genetic as well as heritability trends were generated for fibre diameter, staple length, greasy fleece weight for clip 1 and greasy fleece weight clip 2 from Government Sheep Breeding Farms Kralpathri (1997–2016) and Goabal (2013–2016). Trend lines were generated as linear regression coefficients of mean breeding values, phenotypic values and heritability for animal’s year of birth. Trends obtained for phenotypic values for fibre diameter and greasy fleece weight at clip one were positive. For staple length and greasy fleece weight at second clip slope was found to be negative. Trends were significant for fibre diameter and staple length and insignificant for all other traits. Slopes for fibre diameter, staple length and greasy fleece weight for first clip and greasy fleece weight for second clip were 0.0126±0.0028, –0.052±0.0203, 0.00228±0.00618, – 0.01945±0.0119 respectively. It may, therefore, be concluded the genetic progress may have more or less stagnated over the years and that an effective selection strategy considering the genetic merit of animals may be adopted to sustain the sheep breeding programs for Kashmir Merino breed.